PENGARUH KEMANDIRIAN BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI MATA PELAJARAN EKONOMI DI SMA SWASTA TAMANSISWA PEMATANGSIANTAR - Nurul Aulia Sari; Anggun Tiur Ida Sinaga (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine the effect of learning independence and learning motivation on the learning outcomes of grade XI students in economic subjects at Tamansiswa Pematangsiantar Private High School. The variables in this study are learning independence and learning motivation as independent variables and learning outcomes as the dependent variable. This type of research is quantitative research, with a population of all XI social studies students at Tamansiswa Pematangsiantar Private High School and a research sample of XI social studies students of Tamansiswa Pematangsiantar Private High School consisting of 96 students selected using simple random sampling (slovin formula). Data collection techniques using instruments: (1) learning independence questionnaire, (2) learning motivation questionnaire, and (3) learning outcomes in the form of even semester T.A 2023/2024 UTS scores.The results of this study indicate that: (1) there is a positive and significant effect of learning independence on learning outcomes, this result can be seen in the t test where the tcount value of learning independence (2.377)> ttable value (1.985802) which means that the variable is significant. (2) There is a positive and significant effect of learning motivation on learning outcomes, this can be seen in the t test where the tcount value of learning motivation (2.098)> ttable value (1.985802) which means that the variable is significant. (3) Learning independence and learning motivation together affect learning outcomes, this result can be seen in the F test where the Fcount value (5.569)> Ftable value (3.094337). The R Square coefficient of determination test is known to be 0.107, which means that 10.7% of the learning independence and learning motivation variables affect student learning outcomes at the Tamansiswa Pematangsiantar Private High School, and the remaining 80.3% is the influence of variables not examined in this study.